Blind fault branching and propagation beneath Central Myanmar Basin revealed by high-resolution aftershock location and focal mechanism of the 2019 Mw5.5 YeU earthquake sequence - Oo, Win Shwe Sin (2023)
Accurate and precise location and focal mechanism of aftershocks is a fundamental topic in seismology. However, nearfield seismic observations are usually not available for high-resolution source studies, or even when they are available high frequency waveform analyses are rarely conducted to extract more information. Here we study a unique dense nodal array data acquired by the deployment in the source region of the 2019 Mw5.5 strike-slip earthquake in Central Myanmar Basin (CMB). The network, composed of 20 nodal stations with station spacing of ~5km, was deployed ~2 weeks after the mainshock for ~ 40 days. We applied a machine learning based algorithm (Earthquake-Transformer) to detect 667 events from the dataset. Double difference relocation reveals that these events are distributed between 7 to 16 km in depth with a near E-W trending horizontal distribution, which is consistent with the left-lateral fault plane solution of the mainshock. On the vertical component of most of the stations, we observed a strong phase between P and S arrival times. This is an S-to-P converted phase from a sharp velocity boundary between the basin and the bedrock. The best 1D velocity model constrained by 3-component waveform modelling suggests a sedimentary layer thickness of ~3.5km beneath the stations. To determine the focal mechanism of aftershocks, we conducted high-frequency (up to a few Hz) waveform inversions that result in high quality waveform fits hence robust focal mechanisms of ~ 100 aftershocks with Mw1-2. In these focal mechanisms, ~50% are strike-slip events, ~40% are thrust events and ~10% are normal events, all corresponding to NE-SW oriented compressive stress. The thrust events have strikes oriented mostly in NW-SE direction and have dip angles of ~ 45°. Highly diverse aftershock focal mechanisms suggest the fault system is likely immature. The thrust and normal events indicate that the mainshock rupture had branched into or activated nearby secondary faults, which allow the strike-slip fault to propagate and develop a more complex fault system.